(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
The purpose of the present communication is to provide insights into interlanguage variation in speech act realization by examining the speech act of refusal produced by Serbian-speaking learners of L2 Spanish. Therefore, production data from Serbian learners of L2 Spanish will be collected and compared to those of a native control group as a benchmark. More precisely, the aim is to find out which semantic formulas Serbian learners of L2 Spanish employ when performing refusals in different social status situations and how this relates to the refusals produced by Spanish native speakers. To achieve the goal, a discourse completion task (DCT) will be used and the data will be classified and analysed according to Beebe, Takahashi and Uliss-Weltz’s (1990) taxonomy of refusal strategies.